Complete Genome Sequence Reveals Evolutionary Dynamics of an Emerging and Variant Pathovar of Xanthomonas euvesicatoria. (22nd October 2018) - Bansal, Kanika; Kumar, Sanjeet; Patil, Prabhu B
Abstract: Xanthomonas, a complex group of pathogens, infects more than 400 plants, which is expanding to new hosts causing serious diseases. Genome-based studies are transforming our understanding on diversity and relationship of host-specific members, known as pathovars. In this study, we report complete genome sequence of a novel pathovar Xanthomonas axonopodis pv. commiphorae (Xcom) from India. It causes gumming disease of Commiphora wightii, a medicinally important plant. Genome-based phylogenetic and taxonomic investigation revealed that the pathovar belongs to Xanthomonas euvesicatoria and not X. axonopodis as reported earlier . Interestingly, it is a novel host and novel geographic origin for a X. euvesicatoria pathovar. A core-genome-based phylogenetic analysis resolved the pathovar complex of this species on the basis of their hosts. Interestingly, this pathovar harbors a unique 35-kb plasmid encoding type III effectors and toxin–antitoxin gene that is absent in other X. euvesicatoria pathovars and infects tomato, pepper, rose, onion, philodendron, alfalfa, and citrus plants. The pathovar contains two TAL (transcription activator-like) genes, one on plasmid and another on genomic region with an additional pseudo TAL gene flanked by IS elements in the plasmid. Further, Xcom has acquired a novel set of lipopolysaccharide biosynthesis genes after its divergence from the closely related pathovar that infects rose and supports the role of horizontal gene transfer in hypervariation at this locus in the species. Complete genome sequence of this variant pathovar has provided novel insights into evolution of an emerging pathovar in Xanthomonas and will be valuable resource in pathogenomics of X. euvesicatoria .